Musical Leadership and Societal Transformation: Inspiration and Courage in Action - J. Adler, Nancy; M. Ippolito , Linda (Edukacja Ekonomistów i Menedżerów, 2018)
Music is a form of leadership. Music-based interventions in organizations and society are being used throughout the world, including in situations of extreme conflict and consequence. Artists are going beyond the dehydrated language of economics, politics, and war to achieve goals that have eluded those using more traditional approaches. This article presents musical interventions in Bosnia-Herzegovina, Cyprus, Estonia, Northern Ireland, the Middle East, South Africa, the United States, and Venezuela, in which musicians have had the inspiration and courage to make a difference.T=The radical shift in the structure of the world begs for creativity; it asks us to rethink who we are as human beings… It may be that writers, painters, and musicians have an unprecedented opportunity to be co-creators with society’s leaders in setting a path. For art, after all, is about rearranging us, creating surprising juxtapositions, emotional openings, startling presences, flight paths to the eternal. —Rosamund and Benjamin Zander (1998, p. 7)2Art transforms apathy into action.3 Social scientist Ken Gergen (1999) invites us all to become “poetic activists” (p. 12). Perhaps there is no better label for the use of musical interventions in global and organizational crises than that of poetic activism. Activists, great artists, and great leaders share three fundamental perspectives (Adler, 2006, 2010, 2011, 2015). They all demonstrate the courage to see reality the way it is. They all exhibit the courage to imagine possibility—positivefutures—even when the world labels such imagination as naïve for daring to express optimism. And they all have the courage to inspire people to move from current reality back to possibility.Over the past half-century, with no singular organized movement or unifying philosophy to guide them, artists and artistic processes have attempted to transform reality in numerous contentious situations. In particular, music has been used to address extreme conflict and the threat of conflict, along with the dysfunction and degradation that conflict so often causes (see Tongeren, 1999; Urbain, 2008; Ippolito, 2008).4 Music, most often when combined with other approaches, appears to have produced generative outcomes in some, although not all, situations in which it has been introduced. In many circumstances, musical interventions have inspired the broader community (see Tongeren, 1999; Welch & LeBaron, 2006; Ippolito, 2008; Cohen, Gutiérrez Varea, & Walker, 2011). Such initiatives exemplify the frame-breaking perspectives and approaches that music has the potential to offer.